PARENTAL PERCEPTION ON NEBULIZED MEDICATION AND POTENTIAL REASONS FOR OFF-LABEL USAGE OF DEXAMETHASONE IN CHILDREN FROM ROMANIA - Mihai Craiu; Valentina Daniela Comanici; Iustina Violeta Stan (Amaltea Medical Publishing House, 2017)
Background and aim. In the last decade a significant increase of nebulized medication usage has been documented in Romania. Authors are aiming to describe parental and physician's change of perspective regarding nebulized medication in the new era of online communication and education. Material and methods. Two different questionnaires were posted in a large and representative group (more than 60,000 followers) of Romanian parents and physicians, Virtual Children's Hospital ("Spitalul Virtual de Copii"). Results. More than 4,000 answers were submitted. 94.4% responders confirmed using at least once wetnebulized medication in children. A particular aspect documented was dexamethasone off-label usage via nebulizer in 67.8% children. Additional 7% of responders confirmed that they received an indication to nebulize a normal saline suspension with dexamethasone phosphate for parenteral usage, but they didn't follow the indication and used an approved treatment. Conclusions. Upon our knowledge this is the first large study on nebulized dexamethasone in Romanian literature. 95% of Romanian children receive nebulized medication. Nebulizer is regarded by parents as a simple and friendly tool that can solve virtually all issues related to airway diseases in our country. 75% of children that received nebulized medication had a prescription for off-label use of dexamethasone.